Analisis komparatif efektivitas keamanan dan penerimaan pengguna pada protokol presensi digital berbasis QR code statis dan dinamis - Dwi Purnomo Putro; Mokhamad Solikin; Puput Eka Suryani (UNIB Press, 2026)
QR code–based digital attendance systems are widely used in higher education, yet they continue to face security challenges such as attendance fraud and inaccurate time recording. This study aims to comparatively evaluate the effectiveness of static and dynamic QR code–based attendance protocols by examining system security and user acceptance. A quantitative approach was employed through a field experiment and a survey grounded in the Technology Acceptance Model (TAM), encompassing Perceived Usefulness, Perceived Ease of Use, and Behavioral Intention. Data were analyzed using independent samples t-tests and Cohen’s d effect size measures. The results show that the dynamic QR code protocol significantly outperforms the static QR code across all TAM constructs (p < 0.001), with very large effect sizes (d > 1.0). These findings indicate that enhanced security mechanisms do not reduce usability, but instead strengthen user acceptance and adoption intention.